Some Probability Characteristics Functions of the Solution of Stochastic Fredholm Integral Equation Contains a Known Sine Wave Function - Baghdad Science Journal (مجلة بغداد للعلوم, 2013)
Abstract:In this paper, some probability characteristics functions (moments, variances,convariance, and spectral density functions) are found depending upon the smallestvariance of the solution of some stochastic Fredholm integral equation contains as aknown function, the sine wave function